2010
DOI: 10.1111/j.1468-3083.2009.03478.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐learning digital modules in Dermatology: a pilot study

Abstract: The questionnaire analysis revealed that a majority of the students were comfortable using the module and felt that it encouraged them towards further in-depth self-learning on the concerned topics. The results from the post-test were compared between the test and control sections, using the Student's t-test, which gave a P-value of 0.084 (5% significance level) suggesting that the difference was not significant. Conclusion To conclude, we would like to suggest that the use of a 'play area' like concept couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 9 publications
1
28
0
1
Order By: Relevance
“…A pilot study done in the field of dermatology suggested that interactive IT based self learning modules could be combined effectively with a "play area concept". Although these did not improve student performance in their written examinations, the authors have opined that these modules would promote self-directed learning among students and thus enhance the quality of teaching and learning in dermatology [6]. Similarly, in a study where free online otolaryngology educational modules were provided to residents, quantifiable improvement in examination scores was not noted.…”
Section: Discussionmentioning
confidence: 89%
“…A pilot study done in the field of dermatology suggested that interactive IT based self learning modules could be combined effectively with a "play area concept". Although these did not improve student performance in their written examinations, the authors have opined that these modules would promote self-directed learning among students and thus enhance the quality of teaching and learning in dermatology [6]. Similarly, in a study where free online otolaryngology educational modules were provided to residents, quantifiable improvement in examination scores was not noted.…”
Section: Discussionmentioning
confidence: 89%
“…Os cursos de especialização da rede UNA-SUS são pioneiros no que se refere à formação de especialistas, utilizando a modalidade EAD de forma pura. Estratégias semelhantes ocorrem em diversos países [17][18][19] , a exemplo da estratégia EviMed (www.evimed.net), que promove, cursos sobre diversos tópicos da medicina voltados a educação médica continuada na América Latina e Caribe. Contudo, a maior parte dessas iniciativas constitui-se de cursos autoinstrucionais, nos quais os alunos realizam as atividades de forma autônoma.…”
Section: Discussionunclassified
“…[18,19] Despite this, it is imperative that quality instruction and training be provided to the undergraduates. Modification of OSCE to a computerbased format (CA-OSCE) appears to be an effective and innovative means of doing so.…”
Section: Weakness Of the Studymentioning
confidence: 99%